СОГЛАСОВАННЫЕ И ЗАПЛАНИРОВАННЫЕ ПРОГРАММНЫЕ ЦЕЛИ, НЕЗАВИСИМАЯ ОЦЕНКА И УПРАВЛЕНИЕ ПО РЕЗУЛЬТАТАМ В АФРИКЕ: ПУТЬ К ЗАСЛУЖИВАЮЩИМ ДОВЕРИЯ ОБЯЗАТЕЛЬСТВАМ НИГЕРСКИХ ПОЛИТИКОВ - Икеаниб, Окечукву; Обиоржи, Жозефина; Осадебе, Ннабуике; Угву, Чука (Вопросы государственного и муниципального управления, 2020)
The study examines the application of performance management (PM) to politics in the African context using Nigeria as a focus. It argues that PM will yield better results if it focuses on ways to improve and stabilize the results of politics based on the notion of politics-administration dichotomy and the leadership role of the political class in that relationship. The relevance of some key elements of the Common Assessment Framework (CAF) such as the role of leadership, peer review, self-assessment, competitiveness and comparative learning and innovation are investigated as elements of performance management at this level. Documentary data based on the implementation of the African Peer Review Mechanism (APRM) and evaluation of the application of performance information in relation to those critical roles of politicians were analysed. The authors found that although measures aligning with the CAF model of PM are in place, politicians remain poorly committed, inconsistent and irregular in submitting and using performance information. The study suggests strengthening PM at the political level of governance through energised support for an African Peer Review Mechanism framework and an international push for sustained application of peer review and results of various global performance indexes in dealing with African countries.